Narratives we organise by - Czarniawska-Joerges, Barbara; Gagliardi, Pasquale, 1936- (Advances in organization studies ;, 2003)
This book is a collection of texts that explore the analogy between organizing and narrating, between action and text. The raw material of everyday organizational life consists of disconnected fragments, physical and verbal actions that do not make sense when reported with simple chronology. Narrating is organizing this raw and fragmented material with the help of such devices as plot and characters. Simultaneously, organizing makes narration possible, because it orders people, things and events in time and place. The collection, written by organization researchers from many different countrie.